The effects of repetitive Transcranial Magnetic Stimulation on empathy and impulsivity in healthy adults - Yang, Cheng-Chang (2018)
Both impulsivity and empathy are considered crucial in clinical, in particular forensic, populations. A neuroscientific technique, namely repetitive transcranial magnetic stimulation (rTMS), has proven its therapeutic utility in a variety of neuropsychiatric disorders and may be effective in modulating empathy and impulsivity. This thesis aimed to examine the effects of rTMS on empathy and impulsivity in healthy adults via two systematic reviews with meta-analyses and two empirical rTMS studies, thereby contributing to the relatively small pool of knowledge in the field.